Impacto do acompanhamento de obras públicas utilizando as técnicas de gerenciamento de obras privadas. - Bezerra, Edvaldo Gonçalves (2022)
The study seeks to nurture the municipal public services of several successful techniques used in the management of private works, to improve the performance in the management and control of these services, trying to bring the efficiency of the public service closer to the performance of the management of private services. With this objective, a quantitative research of a qualitative nature will be used, which will be proposed to professionals directly involved in the management and inspection services of municipal public bodies in seven municipalities in the metropolitan region of Recife, through questions that envision opportunities for the insertion of techniques and private management concepts, applied to municipal public works. The objective of this research is that the opinion of the universe of professionals involved in the inspections of public services is known, regarding the contribution of improvement in performance, efficiency and professional transparency of the services provided to taxpayers. Knowing in advance, that this is a small portion of the union, but that it has the possibility of offering parameters to follow and direct future broader studies. However, at the conclusion of possession of the results achieved with the field research, where the wishes of the professionals involved in the inspection will be verified and if there is a relevant contribution to society of the use of private management techniques in public works, bringing and contributing with benefits to society .